DECREASED EXPIRATORY PEAK CURRENT IN COPD PATIENTS WITH BUTEYKO BREATHING TECHNIQUES - Yuniarti, Enny Virda (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Chronic obstructive pulmonary disease is still a threat to the world community COPD will have a negative impact on the health of sufferers. The purpose of this study was to analyze the effect of buteyko breathing on expiratory peak currents in COPD patients. This research is a type of quantitative research with a pre-experimental design through a one group pre-post test design approach. The sample in this study was 58 COPD patients who fit the inclusion criteria. The tools used for data collection are peak flow meters to measure expiratory peak flows and SPO for buteyko breathing exercises. The results of the study included the average value of the peak expiratory current before giving buteyko breathing was 158.34 L / minute with a standard deviation of 69.1899. The average peak expiratory current after buteyko breathing is 144.42 L/min with a standard deviation of 16.21961. The difference in the increase in expiratory peak current before buteyko breathing and after buteyko breathing was 24.91. The paired t test results are p value of 0.001, it was found that there was a significant effect of buteyko breathing on the increase in expiratory peak current of COPD patients. Structured breathing exercises from buteyko exercise have the potential to increase lung capacity, allow for more efficient oxygen uptake, help achieve deeper and more efficient breathing, potentially affect oxygen saturation levels.